PENGARUH PERTUMBUHAN EKONOMI, KEPADATAN PENDUDUK DAN PENGANGGURAN TERHADAP KRIMINALITAS PERKOTAAN ACEH - Rahmat Erija Fajri; Cut Zakia Rizki (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstractThis study aims to analyze how the influence of economic growth, population density and unemployment on crime rates in five cities in Aceh Province. This study uses secondary data, namely data on economic growth, population density, unemployment and crime data in four cities in Aceh Province. The analytical model used is quantitative analysis. The data analysis method in this study is panel data using the Generalized Least Square (GLS) approach. The results of this study indicate that the resulting model is as follows: Cr5,5 = α + βDen5,5 + eit or Cr = –503.1867 + 0.462479Den - 26.83167PDRB + 171.0790UNP. Density or population density variables have a positive and significant effect on crime. This means that the higher the population density, the higher the crime. The variable Perkapita GRDP has a negative and significant effect on crime. This means that the higher the GDP per capita then the crime will decrease. Furthermore, the UNP variable or unemployment has a positive and significant effect on crime. This means that the higher the number of unemployed, the more crime will also increase.Keywords: density, unemployment, economic growth and crime.